2012
DOI: 10.4161/pri.19806
|View full text |Cite
|
Sign up to set email alerts
|

Prion infection promotes extensive accumulation of α-synuclein in aged human α-synuclein transgenic mice

Abstract: In neurodegenerative disorders of the aging population, misfolded proteins, such as PrP(Sc), α-synuclein, amyloid β protein and tau, can interact resulting in enhanced aggregation, cross seeding and accelerated disease progression. Previous reports have shown that in Creutzfeldt-Jakob disease and scrapie, α-synuclein accumulates near PrP(Sc) deposits. However, it is unclear if pre-existing human α-synuclein aggregates modified prion disease pathogenesis, or if PrP(Sc) exacerbates the α-synuclein pathology. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Consistent with this hypothesis is a study in which shorter incubation times to prion disease were observed in transgenic mice that overexpress human A53T α-synuclein compared to non-transgenic controls inoculated with three prion strains [ 18 ]. Another study reported that inoculation of prions into aged transgenic mice overexpressing human wild type α-synuclein resulted in more extensive and abundant intraneuronal and synaptic accumulation of α-synuclein relative to non-transgenic control mice [ 19 ]. In addition, in agreement with the latter mechanism is the observation that CJD patients exhibit impairments of the nigrostriatal pathway, which is a hallmark of Parkinson’s disease [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this hypothesis is a study in which shorter incubation times to prion disease were observed in transgenic mice that overexpress human A53T α-synuclein compared to non-transgenic controls inoculated with three prion strains [ 18 ]. Another study reported that inoculation of prions into aged transgenic mice overexpressing human wild type α-synuclein resulted in more extensive and abundant intraneuronal and synaptic accumulation of α-synuclein relative to non-transgenic control mice [ 19 ]. In addition, in agreement with the latter mechanism is the observation that CJD patients exhibit impairments of the nigrostriatal pathway, which is a hallmark of Parkinson’s disease [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many more putative cross-reactivity reactions between aS and human amyloidogenic proteins that await to be mechanistically assessed in vitro. For example, expression of a mutant SOD1 (amyloidogenic protein in ALS) in cells promoted cellular aS aggregation [84] and inoculation of infectious prions into aS-expressing transgenic mice promoted extensive aS aggregate deposits and exacerbated aS pathology [85]. These studies hint to possible cross-reactivity on the molecular level such that, in both cases, interaction with the other protein (as monomer or amyloid) would accelerate aS aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased α‐syn aggregation may lead to defective protein clearance and autophagy deficits and, therefore, to increased release of α‐syn to the extracellular environment and consequent spreading. The prion‐like characteristics of α‐syn aggregates may also lead to abnormal α‐syn conformational changes and trigger its accumulation in acceptor cells . Therefore, it follows that α‐syn‐centric therapies should target one or more of these dysregulated mechanisms to effectively reduce α‐syn pathology.…”
Section: Novel Therapies Targeting α‐Syn In Msa and Related Disordersmentioning
confidence: 99%